Synthesis and Optimization of Ni-Based Nano Metal–Organic Frameworks as a Superior Electrode Material for Supercapacitor - Singh, D; Navarrete-Villegas, A; Manquián-Villalobos, C; Vivas, L (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Metal–organic frameworks (MOFs) are hybrid materials that are being explored as active electrode materials in energy storage devices, such as rechargeable batteries and supercapacitors (SCs), due to their high surface area, controllable chemical composition, and periodic ordering. However, the facile and controlled synthesis of a pure MOF phase without impurities or without going through a complicated purification process (that also reduces the yield) are challenges that must be resolved for their potential industrial applications. Moreover, various oxide formations of the Ni during Ni-MOF synthesis also represent an issue that affects the purity and performance. To resolve these issues, we report the controlled synthesis of nickel-based metal–organic frameworks (NiMOFs) by optimizing different growth parameters during hydrothermal synthesis and by utilizing nickel chloride as metal salt and H2bdt as the organic ligand, in a ratio of 1:1 at 150 °C. Furthermore, the synthesis was optimized by introducing a magnetic stirring stage, and the reaction temperature varied across 100, 150, and 200 °C to achieve the optimized growth of the NiMOFs crystal. The rarely used H2bdt ligand for Ni-MOF synthesis and the introduction of the ultrasonication stage before putting it in the furnace led to the formation of a pure phase without impurities and oxide formation. The synthesized materials were further characterized by powder X-ray diffraction (XRD) technique, scanning electron microscopy (SEM), and UV–vis spectroscopy. The SEM images exhibited the formation of nano NiMOFs having a rectangular prism shape. The average size was 126.25 nm, 176.0 nm, and 268.4 nm for the samples (1:1)s synthesized at 100 °C, 150 °C, and 200 °C, respectively. The electrochemical performances were examined in a three-electrode configuration, in a wide potential window from −0.4 V to 0.55 V, and an electrolyte concentration of 2M KOH was maintained for each measurement. The charge–discharge galvanostatic measurement results in specific capacitances of 606.62 F/g, 307.33 F/g, and 287.42 F/g at a current density of 1 A/g for the synthesized materials at 100 °C, 150 °C, and 200 °C, respectively. © 2024 by the authors.